Advances in the understanding of poor graft function following allogeneic hematopoietic stem-cell transplantation. (August 2020) - Chen, Juan; Wang, Hongtao; Zhou, Jiaxi; Feng, Sizhou
Poor graft function (PGF) following allogeneic hematopoietic stem-cell transplantation (allo-HSCT) is a life-threatening complication and is characterized by bilineage or trilineage blood cell deficiency and hypoplastic marrow with full chimerism. With the rapid development of allo-HSCT, especially haploidentical-HSCT, PGF has become a growing concern. The most common risk factors illustrated by recent studies include low dose of infused CD34 + cells, donor-specific antibody, cytomegalovirus infection, graft versus host disease (GVHD), iron overload and splenomegaly, among others. Because of the poor prognosis of PGF, it is crucial to uncover the underlying mechanism, which remains elusive. Recent studies have suggested that the bone marrow microenvironment may play an important role in the pathogenesis of PGF. Deficiency and dysfunction of endothelial cells and mesenchymal stem cells, elevated reactive oxygen species (ROS) levels, and immune abnormalities are believed to contribute to PGF. In this review, we also discuss recent clinical trials that evaluate the safety and efficacy of new strategies in patients with PGF. CD34 + -selected stem-cell boost (SCB) is effective with an acceptable incidence of GVHD, despite the need for a second donation. Alternative strategies including the applications of mesenchymal stem cells, N-acetyl-l -cysteine (NAC), and eltrombopag have shown favorable outcomes, but further large-scale studies are needed due to the small sample sizes of the recent clinical trials.